Children's creative thinking abilities and social orientations in Finnish early childhood education and care. Issue 6 (26th April 2022) - Nikkola, Teemu; Reunamo, Jyrki; Ruokonen, Inkeri
ABSTRACT: The study presented in this article is part of a larger study called Progressive Feedback (blogs.helsinki.fi/orientate), which is an early childhood education and care (ECEC) research and development project. The aim of this article is to find out (a) how childreńs tested creative thinking abilities, fluency, originality and imagination correlated with childreńs social orientations in kindergarten and (b) how childreńs participative orientations occur in relation with the teacher and peers. The data consist of Reunamo's child interview tool and the Thinking Creatively in Action and Movement (TCAM) test. The data (280 children from 23 kindergartens and pre-primary schools) were gathered from two municipalities in southern Finland. The results show that the participative orientation was strongly connected with creative thinking abilities, but it was rare in social situations concerning adults. In participative orientation, children concern the situation and intend to change it.